Modelling systemically important banks vis-à-vis the basel prudential guidelines - M. Zulkifli Salim; Kevin James Daly (Journal of Risk and Financial Management, 2021)
Our paper investigates Indonesia's systemically important banks (SIBs) using theoretical approaches-CoVaR, marginal expected shortfall (MES), and SRISK-to compare with the Basel guidelines as benchmark. We use Indonesian banks' market and supervisory data over the 2008-2019 period. The research aims to seek intertheoretical model interaction and SIB ranking in concordance with the Basel guidelines as applied by a bank supervisor. The findings show that SRISK produced a more consistent ranking compared with CoVaR and MES. CoVaR and MES had higher intermodel correlation converted to 59% similarity in rankings. Further, all theoretical models are in line with the Basel guidelines, where the closest approximation is at 47%. The results indicate that policy makers could use scholarly models as validation tools and help improve supervision decision to identify systemically important institutions.
Keywords: G21; G210; G28; G280; 330; bank supervision; Basel; risk modelling; systemic bank; systemic risk